Impact of Blood Pressure After Successful Endovascular Therapy for Anterior Acute Ischemic Stroke: A Systematic Review - Maïer, Benjamin; Delvoye, François; Labreuche, Julien; Escalard, Simon; Desilles, Jean-Philippe; Redjem, Hocine; Hébert, Solène; Smajda, Stanislas; Ciccio, Gabriele; Lapergue, Bertrand; Blanc, Raphaël; Piotin, Michel; et al. (Frontiers in Neurology, 2020)
Background and Purpose- Optimal blood pressure (BP) targets after endovascular therapy (EVT) for acute ischemic stroke (AIS) still need to be assessed, especially according to the recanalization status. Facing the lack of randomized controlled trials addressing this question, we performed a systematic review of studies assessing the post-EVT BP impact on functional outcome and symptomatic intracranial hemorrhage (sICH). Methods- Studies published after January 1st 2012 were included in the systematic review. The PRISMA checklist and flow diagram were followed for the design and reporting of this work. Results- Seventeen studies were included in the present analysis. Despite a significant heterogeneity among studies which precluded a meta-analysis, systolic BP (SBP) was the most frequently used parameter to describe BP. BP variability (standard deviation, successive variability) after EVT was associated with worse functional outcome, especially in studies without specific BP targets after successful EVT. Lower BP values after successful EVT were associated with lower odds of sICH. Four studies evaluated the post-EVT BP impact on recanalized patients solely, with only one specifically addressing the impact of a TICI 2B vs. 2C. Interestingly, SBP reduction was inversely associated with worse outcomes in TICI 3 patients but not in TICI 2B patients, pointing to the potential value of BP management according to the exact TICI. Conclusions- BP post-EVT seem to be associated with worse functional outcomes and sICH. The important heterogeneity depicted among the included studies underline the urgent need of randomized controlled trials evaluating this question.